Development, Evaluation, and impLemenTation for guideline adaptation: a quality improvement protocol for the DELTA study in global health practice - Shu Wang; Yuan Zhang; Zhixuan Wen; Yueming Yang; Yuxuan Zhang; Yixiong Geng; Yali Liu; Jianguo Zhang (BMC, 2023)
Abstract Background Guideline adaptation is an emerging field to provide more appropriate recommendations for local clinical practice quality and to promote global health equity. However, its utilization status, adaptation procedures, and related materials remain to be studied. Methods This study developed a quality improvement protocol for a study as the Development, Evaluation, and impLemenTation for guideline Adaptation (DELTA) study. Current adapted clinical practice guidelines (CPGs) will be systematically searched. Their characteristics, utilization status, and adaptation procedures will be extracted, compared, and analyzed. Whether these adapted CPGs rigorously followed the instruments and steps of adaptation frameworks will also be appraised. In addition, the advantages and limitations of current adaptation methods and their suitable application situations will be analyzed. In addition, future perspectives as DELTA series and DELTA system, aiming for comprehensively evaluating current needs for guideline adaptation and developing a unified framework and related materials were proposed to improve the acceptability, applicability, and implementation of guideline adaptation in clinical practice. The DELTA series are divided into four phases: phase I in analyzing status, characteristics, and procedures and completeness of adapted CPGs; phase II in analyzing differences, heterogeneity, and implementation between adapted and original CPGs; and phase III in collecting, analyzing, and comparing all available adaptation materials. With these research bases, an international working group will be established in phase IV and will develop unified guideline adaptation materials after Delphi consensus, including adaptation frameworks, appraisal tools and checklists, registries, and databases. Discussion Guideline adaptation has been advanced as an efficient way to guide local clinical practice. However, it still faces several major challenges. The proposed DELTA study, series, and system will further contribute to this emerging topic. Trial registration: This study has been registered by the PROSPERO international database. https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=400170 .